الاغتراب النفسي وعلاقته بتقدير الذات دراسة ميدانية لدى عينة من طلبة جامعة دمشق القاطنين بالمدينة الجامعية - الزحيلي, غسان; الملحم, سجان محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث الحالي إلى كشف العلاقة الارتباطية بين الاغتراب النفسي وتقدير الذات لدى طلبة مدينة الشهيد باسل الأسد الجامعية في دمشق والكشف عن الفروق بين متوسط درجاتهم على مقياس الاغتراب النفسي ومقياس تقدير الذات تبعاً للمتغيرات التالية(الجنسية- المستوى الدراسي). وتم استخدام الأدوات التالية: مقياس الاغتراب النفسي إعداد نعيسة(2012), ومقياس تقدير الذات إعداد جعفر(2007). وتكونت عينة البحث من (672) طالباً وطالبة من طلبة مدينة السكن الجامعي. ومن أهم النتائج التي توصل اليها البحث: وجود علاقة ارتباطيه عكسية سلبية ذات دلالة إحصائية بين درجات الطلبة على مقياس الاغتراب النفسي ودرجاتهم على مقياس تقدير الذات. عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس الاغتراب النفسي تُعزى إلى متغير المستوى الدراسي. وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس الاغتراب النفسي تُعزى إلى متغير الجنسية لصالح الطلبة العرب. وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس تقدير الذات تُعزى إلى متغير المستوى التعليمي لصالح طلبة "الدراسات العليا". وجود فروق ذات دلالة إحصائية بين متوسطات درجات الطلبة على مقياس تقدير الذات تُعزى إلى متغير الجنسية لصالح الطلبة السوريين. This research aims at present to detect the correlation between the Psychological Alienation and the self-esteem, as well as to detect differences between the average scores students, undergraduate and graduate, at the scale of psychological Alienation and a measure of self-esteem among faculty members according to the following varieties: (Nationality-level of education) among the students of the city of the Martyr Basil al-Assad in Damascus. To achieve this goal, the following tools have been used: Questionnaire to Measure the Psychological Alienation, prepared by Ragdaa Naaisa (2012); and a questionnaire to measure the phenomenon of Self-esteem by Gaafer (2007). The study sample consists of (672) male and female students from staying on campus. The most important findings of Search: · There is a counterproductive negative statistically significant correlation between the scores of students on a scale of psychological alienation and grades the a scale of Self-esteem. · Lack of statistically significant differences among the average scores of students on the scale of psychological alienation due to the variable educational level. · There are differences, statistically, between average degrees of students on the scale of of psychological alienation due to the variable of nationality of the Arab students. · There are differences among average scores of students on the scale of the self variable, due to the change of the teaching level of the "postgraduate" students. · There are differences between the mean scores of students on a scale of Self-esteem due to the variable in favor of the Syrian Nationality.